Strengthening Digital Citizenship Through an Islamic Values-Based Media Literacy Program at SMPIT Istiqomah Bungursari - Muhamad Hanif Fuadi; Fakhri Adi Aminudien; Frista Fitriany Ramadhanita (Dedikasi Sosial: Jurnal Pengabdian Masyarakat, 2025)
Digital transformation in education presents significant challenges and opportunities, particularly for Islamic educational institutions seeking to foster responsible digital citizenship among students. This community service program aimed to strengthen digital citizenship through an Islamic values-based media literacy program at SMPIT Istiqomah Bungursari, Tasikmalaya City. The program utilized a participatory action research approach involving 52 students aged 12-15 years, 10 teachers, and three school administrators over 4 months. The intervention consisted of 16 structured sessions (2 hours each) that employed a blended learning methodology, integrating traditional Islamic pedagogical approaches with modern digital literacy techniques. Results demonstrated significant improvements in students' digital citizenship competencies, including a 40% increase in hoax identification abilities (from 45% to 85%), enhanced ethical digital communication skills (36% improvement), and strengthened inclusive attitudes in digital interactions. The program successfully achieved equitable participation across gender and grade levels, with consistent improvement rates of 40-42% across all demographic groups. The developed "Literasi Setara" (Equal Literacy) model proved effective in creating an inclusive learning environment that maintains Islamic identity while developing critical digital skills. This community service program concludes that integrating Islamic values with digital literacy education effectively develops responsible digital citizens who can navigate the digital world while preserving their religious and moral foundations.